Brand management - Sagar, Mahim (Ane Books Pvt. Ltd., 2009)
This book is the outcome of a decades research in brand management. It will provide a platform for learning product and brand management in Indian context. The main purpose of this book is that it will serve as a Fundamental Textbook of Brand Management for all management students at both UG and PG levels who wish to specialize in Marketing and or Brand Management. Core elements of brand management have been identified, namely like Brand Identity, Brand Image, Brand Personality, Brand Awareness, Brand Positioning & Brand Equity and so on. The application of these elements are being elaborated and explained with the help of various case studies of global as well as Indian Brands. This book will fulfill long felt need of students as well as managers for a structured textbook on Brand Management. The authors hope that the readers would be benefited from the book and would find it useful in developing an understanding of Brand Management.